The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Hollow Zr-MOF/Bi NPs@MXene heterojunction-based ECL amplification strategy for detection of childhood asthma-related miRNA-143-3p - Yang Gao; Zhenrun Li; Wenyan Li; Fangru Jia; Linlin Ma; Qiang Ma; Yanan Li (Chemical Engineering Journal, 2026)

Boosting CO₂ sequestration and lipid production in microalgae via a dual-ligand MOF bio-hybrid strategy - Longfei Yuan; Mengwei Li; Xinqing Gao; Manrong Wu; Yitong Wu; Yiming Li; Jianjun Liao; Ping Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Tackling antibiotic resistance genes as environmental contaminants: Innovations in advanced oxidation processes and strategic solutions - Chen Gao; Liang Zhang; Linlin Zang; Hian Kee Lee; Sheng Tang (Journal of Environmental Sciences, 2026)

Positive covariance between temperature and precipitation affects dendroclimatological reconstructions - Linlin Gao; Tatiana Bebchuk; Clive Oppenheimer; Timothy J. Osborn; Jan Esper; Mirek Trnka; Xiaohua Gou; Yang Deng; Ulf Büntgen (Global and Planetary Change, 2026)

Engineering carbon dots with amplified peroxidase-mimetic activity for dual-modal colorimetric-photothermal sensing of organophosphorus and carbamate pesticides - Na Gao; Yajuan Zhao; Yuhan Huang; Yanke Zhou; Linlin Yang; Liguo Ji; Hao Zhu; Wenjie Ren; Guangjie He (Analytica Chimica Acta, 2026)

Numerical simulation and improvement of the temperature rise evolution during the Cryo-compressed hydrogen filling process in type III vessels - Linlin Gao; Haocheng Wang; Bo Tang; Teng Zhang; Xueqiang Dong; Maoqiong Gong (International Journal of Refrigeration, 2026)

Insights into Cronobacter sakazakii adaptation to Benzalkonium chloride: virulence assessment and transcriptomics analysis - Hongmei Niu; Xiang Wang; Yuan Wang; Xiaojie Qin; Lei Fang; Jianwen Gao; Yanqi Zhou; Linlin Xiao; Qingli Dong (Food Research International, 2026)

A barnacle-inspired hydrogel enables external-internal synergistic modulation of NF-κB/Nrf2 signaling for diabetic wound healing - Xuetong Ji; Junyao Li; Xintao Gao; Jiqing Dong; Linlin Ma; Yu Han; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

Identification of Fertility and Internal Genetic Uniformity in Monogerm Sugar Beet Hybrid Combinations - Chengwei Zhang; Rui Gao; Gaofei Lü; Zedong Wu; Linlin Sun (Sugar Tech, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

A first quantitative assessment of seabed litter collection efficiency using bottom otter trawls and fishery depletion models - Yue Chen; Xinxing You; Linlin Gao; Huaxiang Sheng; Yipu Sui; Xinle Xu; Liuyi Huang (Environmental Pollution, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Similarity-based classification of groundwater hydrographs to reveal regional groundwater dynamics patterns in a semi-arid agricultural area - Xiangbo Meng; Xi Chen; Yonggen Zhang; Man Gao; Linlin Lu (Hydrogeology Journal, 2026)

Performance research of the natural sand grains for adsorption enrichment and removal of Cd(II) from aqueous solution - Jiaxiang Qi; Yixin Sui; Shuaibing Gao; Linlin Chai; Shawket Abliz (Environmental Science and Pollution Research, 2026)

KansFormer network based on a multimodal cross-attention mechanism for drug-target interaction prediction - Anting Gao; Yuandong Liu; Kai Che; Longbo Zhang; Yifeng Gao; Linlin Xing (Molecular Diversity, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

Bioaugmentation of thiourea-acclimated biomass relieves thiourea’s inhibition of nitrification - Meng Huang; Xiaobing Gao; Ning Yan; Fei Liu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2026)

Engineering the 1T/2H-MoSe2 phase junction as an S-scheme cocatalyst for boosted photocatalytic hydrogen evolution - Linlin Gao; Yamei Huang; Jiayi Meng; Yifan Liao; Zizheng Wang; Quanmei Zhou; Yuchen Wei; Wei-Lin Dai (Journal of Environmental Chemical Engineering, 2026)

Spectral reconstruction of multichannel fluorescence for rapid assessment of TVB-N in meat products - Qian You; Wenhong Gao; Zhong Han; Xin-an Zeng; Linlin Ye; Yuwen Huang; Yunqi Zhang; Ji Ma (Food Chemistry, 2026)

Cyclic performance of dual stage energy dissipation joints for connecting CFST column and exterior wide-flat beam - Mingyang Wei; Linlin Song; Jianhua Zhang; Cheav Por Chea; Yan Geng; Xueming Zhang; Dianwei Gao; Zhicheng Liu (Engineering Structures, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Advances in the effect of the structure of high-moisture extruded plant-based meat on in vitro digestive properties - Yuyang Huang; Yixin Zhang; Yang Gao; Ying Zhu; Bingyu Sun; Linlin Liu; Jiyuan Liu; Baoning Zheng; Mingshou Lv; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2026)

Damage and Creep Response of Tunnel Lining Concrete at Elevated Temperatures - Linlin Yao; Linlin Gu; Zhen Wang; Zhiquan Huang; Fei Gao (Geotechnical and Geological Engineering, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Research on forecasting and analysis methods for ship deck icing in polar regions - Zhenze Yang; Zhenju Chuang; Linlin Yin; Yijie Zhao; Nan Gao (Ocean Engineering, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Unveiling structural evolution during high-moisture extrusion of soy protein isolate-wheat gluten systems with soy dietary fiber: A sudden shutdown-based study - Ruqi Guo; Haojia Zhang; Yang Gao; Zihan Wang; Yinlin Wang; Ying Zhu; Linlin Liu; Xiuqing Zhu (Food Chemistry, 2026)

A novel bacteriophage pAEh1 for controlling Aeromonas hydrophila infection in aquaculture - Sifan Jiang; Boyang Zhou; Tongping Zhang; Rongsi Dai; Su Long; Linlin Yang; Mingwang He; YanJiao Fu; Jiajing Guo; Zhipeng Gao (Fish & Shellfish Immunology, 2026)

Physiological changes in carbon sequestration and lipid production characteristics of microalgae under high CO2 domestication - Xinqing Gao; Longfei Yuan; Hui Yin YEONG; Guangze Lv; Xiangya Zhang; Xiaodong Zhang; Linlin Zhang; Jianjun Liao (Environmental Science and Pollution Research, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

June–September mean temperature variability in the eastern Qinghai-Tibet Plateau over the past 225 years based on high quality tree-ring records - Xinyue Li; Linlin Gao; Baolong Ma; Kai Wang; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mitigating iron contamination in cyanide gold extraction: Ceramic grinding media for enhanced efficiency and reduced cyanide consumption - Qianfei Zhao; Yuhai Zhang; Peng Gao; Linlin Tong; Yuexin Han; Hongying Yang; Shuai Yuan (Minerals Engineering, 2025)

Transition cavity structure and SPI-WG ratios mediated the porous fibrous structural morphology changes of high-moisture extrudates - Yang Gao; Yihan Song; Ying Zhu; Yuyang Huang; Linlin Liu; Lianzhou Jiang; Xiuqing Zhu (Food Research International, 2025)

Superior bridging effect of Pt NPs in all-solid-state Z-scheme CdS QDs/NaTaO3 microcube heterojunction for highly efficient photocatalytic hydrogen evolution - Jiayi Meng; Juhua Zhang; Yamei Huang; Zizheng Wang; Yifan Liao; Quanmei Zhou; Yuchen Wei; Linlin Gao; Wei-Lin Dai (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

How do atmospheric pollutant changes driven by anthropogenic heat provide feedback on the urban thermal environment in Beijing? - Jiangkang Qian; Linlin Zhang; Xinran Zhu; Qingyan Meng; Xinli Hu; Jianfeng Gao; Shize Chen (Sustainable Cities and Society, 2025)

Gaussian Building Mesh (GBM): Extract a building’s 3D mesh with Google Earth and Gaussian Splatting - Kyle Gao; Dening Lu; Hongjie He; Liangzhi Li; Linlin Xu; Michael A. Chapman; Jonathan Li (Remote Sensing Applications: Society and Environment, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Earlywood blue intensity of Picea purpurea reveals June minimum temperature variability in Eastern Tibetan Plateau since 1671CE - Na Du; Shuhua Qiao; Baolong Ma; Xinyue Li; Linhan Si; Linlin Gao; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Enhanced selective oxidation of 5-Hydroxymethylfurfural with a recyclable V34@Fe3O4/C catalyst Enriched with Mixed-valence polyoxovanadate active centers - Chunhui Zhang; Mengqi Wang; Changhao Zhao; Junpeng Wang; Yundong Cao; Linlin Fan; Hong Liu; Guang-Gang Gao (Fuel, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Waste asphalt-derived hard carbon assisted by biomass templating for sodium-ion batteries - Danqing Li; Xin He; Linlin Wang; Yinghao Zhang; Xingqiao Wu; Mei Ding; Chunhui Gao; Yang Gao; Chuankun Jia (Chemical Engineering Journal, 2025)

Assessing Intra-Annual Spatial Distribution of Amphioctopus fangsiao in the East China Sea and Southern Yellow Sea Using Ensemble Models - Yan Cui; Xiaodi Gao; Shaobo Yang; Shengfa Li; Linlin Yang (Journal of Marine Science and Engineering, 2025)
Understanding the distribution pattern and its drivers of species is crucial for developing effective and sustainable management strategies. Amphioctopus fangsiao is the octopus of significant commercial and ecological value along the coast of China, with multiple distinct populations. However, research on their ecological dynamics remains limited and requires further investigation. Here, ensemble models were constructed to examine the spatio-temporal distribution and inter-populational differentiation in environmental adaptability of A. fangsiao in the East China Sea (ECS) and the South Yellow Sea (SYS). Specifically, we generated the ensemble models by integrating Gradient Boosting Machine (GBM), Generalized Linear Models (GLMs), and Maximum Entropy Models (MaxEnt) for the different populations across four seasons, using fishery-independent data collected from 2015 to 2021. The results revealed two hotspots of A. fangsiao in the ECS and SYS: one is the area of SYS along the coastal waters, with latitudes 33° N–34° N and longitudes 120° E–122° E (northern population, NP); the other one is near the Kuroshio-adjacent area with latitudes 28.5° N–29° N and longitudes 123° E–124.5° E (southern population, SP). Both NP and SP exhibited distinct seasonal habitat preferences, with key environmental drivers showing seasonal variations. The NP tended to inhabit coastal waters with lower sea surface heights (SSHs), shallower water depth, and a narrower sea bottom salinity range (SBS). In contrast, SP preferred marine environments with a thicker mixed layer thickness (MLT) and higher concentrations of bottom chlorophyll-a (Chl_b). The environmental characterization of suitable habitats revealed distinct patterns in resource utilization and environmental adaptation strategies between the two populations. This study provides fundamental data for understanding A. fangsiao population dynamics and underscores the importance of considering population-specific habitat preferences within dynamic marine environments.

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

The roles of Paracoccus huijuniae for enhancing denitrification with N-methyl pyrrolidone as the electron donor - Meng Huang; Songyun Chen; Fei Liu; Haiyun Zhang; Xiaobing Gao; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Polysaccharides from traditional Chinese medicine and their nano-formulated delivery systems for cancer immunotherapy - Linlin Sun; Yuting Liu; Qihui Sun; Guimei Wang; Baoxiang Du; Bodong Liu; Tian Gao; Pan Zhao; Yong Yang; Rong Rong (Carbohydrate Polymers, 2025)

The Receptor for Advanced Glycation End-products in the Mouse Anterior Cingulate Cortex is Involved in Neuron‒Astrocyte Coupling in Chronic Inflammatory Pain and Anxiety Comorbidity - Wei Jiang; Minmin Gong; Linlin Shen; Chenghui Yu; Huaizhen Ruan; Penghui Chen; Shihao Gao; Zhi Xiao (Molecular Neurobiology, 2025)

Cover Image - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
The cover image is based on the article Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control by Zhipeng Gao et al., https://doi.org/10.1111/raq.70024 . image

Phage‐Based Biocontrol Strategies and Application in Aquatic Animal Disease Prevention and Control - Linlin Yang; Weiming Zhong; Tao Tang; Mingwang He; Tongping Zhang; Boyang Zhou; Yulong Yin; Jiajing Guo; Zhipeng Gao (Reviews in Aquaculture, 2025)
Aquaculture is essential for meeting future demands for food, yet it faces significant losses from infectious bacterial diseases. Aquaculture has recently been critically imperiled by the emergence of multi‐drug‐resistant bacteria, as it relies significantly on the use of antibiotics for prevention and treatment. The emergence of multidrug‐resistant bacteria poses a critical threat to aquaculture, which heavily relies on antibiotics for prevention and treatment. Bacteriophage (phage) therapy has regained attention with the spread of drug‐resistant bacteria. Phages are viruses that specifically infect bacteria and archaea. As a promising therapeutic strategy for aquatic bacterial diseases, phage therapy offers strong specificity, low resistance potential, rapid metabolism, ease of development, and cost‐effectiveness. In this review, we discuss the advantages, opportunities, and challenges of phage therapy, summarizing the status of research and highlighting emerging technologies aimed at enhancing phage therapy in aquaculture. Finally, the review looks to the future, identifying scientific and technological advances necessary to establish phage therapy as a viable and universal alternative to antibiotics in aquaculture.

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

3D semantic segmentation: Cluster-based sampling and proximity hashing for novel class discovery - Jing Du; Linlin Xu; Lingfei Ma; Kyle Gao; John Zelek; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Evaluation of the virulence characteristics of ST11 Salmonella enterica from different sources using a 2D cell model - Linlin Xiao; Yulin Long; Binru Gao; Ying Hu; Tantao Zhang; Qian Xiao; Xiaojie Qin; Xuejuan Xia; Xiang Wang; Zhuosi Li; Qingli Dong (International Journal of Food Microbiology, 2025)

Rational design of micro-cone array on copper host for dendrite-free sodium metal plating - Mengyang Xu; Chengwen Gao; Tsz Wing Tang; Linlin Zhang; Jiawen You; Xing Zhou; Mengjia Xu; Jang-Kyo Kim; Zhengtang Luo (Chemical Engineering Journal, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

Characterization and adsorption properties of nickel ion-imprinted composites using Silane-modified sand grains as carriers - Shuaibing Gao; Yixin Sui; Anwar Mamat; Linlin Chai; Shawket Abliz (Journal of Water Process Engineering, 2025)

Impact of urban land use and anthropogenic heat on winter and summer outdoor thermal comfort in Beijing - Jiangkang Qian; Linlin Zhang; Uwe Schlink; Xinli Hu; Qingyan Meng; Jianfeng Gao (Urban Climate, 2025)

Multi-perspective evaluation framework of three-dimensional cooling and energy saving potential of urban parks based on numerical simulation - Jianfeng Gao; Linlin Zhang; Qingyan Meng; Xinli Hu; Stephen J. Livesley (Sustainable Cities and Society, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

How to optimize urban blue space to maximize its cooling benefits? A case study in megacity of Beijing - Linlin Zhang; Qingyan Meng; Shun Yao; Jiangkang Qian; Jianfeng Gao; Jiahao Wu (Building and Environment, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Impact of chlorantraniliprole on honey bees: Differential sensitivity and biological responses in Apis mellifera and Apis cerana - Wenmin Li; Yikun Zan; Tong Wu; Sa Yang; Linlin Liu; Shanshan Li; Pingli Dai; Jing Gao (Science of The Total Environment, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

N18 ring: A building block for constructing 1D and 2D polymeric nitrogen frameworks - Yuxiang Gao; Ying Zhang; Shuang Liu; Bo Jin; Linlin Guo; Xu Guo; Zhen Yao; Peng Wang; Bingbing Liu (Science Bulletin, 2024)

Evaluation of Tembusu virus single-round infectious particle as vaccine vector in chickens - Yunzhen Huang; Zhe Liu; Junqin Zhang; Jiawen Dong; Linlin Li; Yong Xiang; Ruihuan Kuang; Shimin Gao; Minhua Sun; Yongjie Liu (Veterinary Microbiology, 2024)

The role of trade policy uncertainty on contemporaneous and lagged connectedness between critical raw materials and high-tech markets: Evidence from China - Wang Gao; Linlin Zhang; Haizhen Zhang; Hongwei Zhang (Resources Policy, 2024)

Exosomal miR-129-2-3p promotes airway epithelial barrier disruption in PM2.5-aggravated asthma - Caihong Wang; Zeyu Niu; Yan Zhang; Nannan Liu; Xiaotong Ji; Jiayu Tian; Linlin Guan; Dongxing Shi; Huiqiu Zheng; Yuhui Gao; Lifang Zhao; Wenping Zhang; et al. (Journal of Environmental Management, 2024)

Molecular epidemiological investigation of Salmonella isolated from the environment, animals, foods and patients in China - Linlin Xiao; Xiaojie Qin; Hu Xiao; Yuehua Gao; Tanmei Sun; Xiaolu Dong; Yulin Long; Xuejuan Xia; Zhuosi Li; Xiang Wang; Qingli Dong (Food Research International, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

Finer topographic data improves distribution modeling of Picea crassifolia in the northern Qilian Mountains - Xiang Zhang; Linlin Gao; Yu Luo; Yiyun Yuan; Baolong Ma; Yang Deng (Journal of Mountain Science, 2024)

Degradation of mycotoxins by pulsed light and evaluation of the safety of degradation products - Lige Qi; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhouli Wang; Xubo Zhao (Journal of Food Engineering, 2024)

Immobilization of pancreatin based on ultrasound-assisted polydopamine functionalized magnetic porous chitosan for the detoxification of ochratoxin A in wine - Saiqun Wang; Tianmin Guo; Xiaoxue Mei; Xinyi Zhong; Linlin Gao; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Chemistry, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Seasonal aridity regulates drivers and temporal variability of wood phenology: A meta-analysis of dendrometer monitoring data across the Northern Hemisphere - Yuhang Zhang; Linlin Gao; Yang Deng; Qianling Huang; Yiyun Yuan; Xingying Shi; Xiaohua Gou (Dendrochronologia, 2024)

A tree-ring based streamflow reconstruction for the Taohe River (Gannan Plateau, China) associated with the Asian-Pacific Oscillation since 1325 CE - Xingying Shi; Linlin Gao; Yang Deng; Yuhang Zhang; Xiang Zhang; Xiaohua Gou (CATENA, 2024)

Control of postharvest soft rot of green peppers by Bacillus subtilis through regulating ROS metabolism - Peipei Feng; Xiaoyun Zhang; Esa Abiso Godana; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Linlin Gao; Jun Li; Lina Zhao; Hongyin Zhang (Physiological and Molecular Plant Pathology, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Quantifying the environmental synergistic effect of cooling-air purification-carbon sequestration from urban forest in China - Rundong Feng; Shenghe Liu; Fuyuan Wang; Kaiyong Wang; Ping Gao; Linlin Xu (Journal of Cleaner Production, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Coupled cooling effects between urban parks and surrounding building morphologies based on the microclimate evaluation framework integrating remote sensing data - Qingyan Meng; Jianfeng Gao; Linlin Zhang; Xinli Hu; Jiangkang Qian; Tamás Jancsó (Sustainable Cities and Society, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Interactive effects of dinotefuran and Nosema ceranae on the survival status and gut microbial community of honey bees - Linlin Liu; Min Shi; Yanyan Wu; Xianbing Xie; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2024)

Asymmetric impacts of El Niño-Southern Oscillation on summer temperature over the eastern Qinghai-Tibetan Plateau, as revealed by the blue intensity of Picea purpurea - Shuhua Qiao; Yang Deng; Linlin Gao; Yiyun Yuan; Qianling Huang; Xiaohua Gou (Global and Planetary Change, 2024)

Impact analysis of hydraulic residence time and dissolved oxygen on performance efficiency and microbial community in N, N-dimethylformamide wastewater treated by an AnSBR-ASBR - Yuchen Wang; Linlin Cao; Yiying Lu; Junjie Liao; Yuxiang Lu; Chengyuan Su; Shu Gao (Environmental Pollution, 2024)

The mediation effect of asprosin on the association between ambient air pollution and diabetes mellitus in the elderly population in Taiyuan, China - Lulu Song; Yuhui Gao; Jiayu Tian; Nannan Liu; Halimaimaiti Nasier; Caihong Wang; Huiqiu Zhen; Linlin Guan; Zeyu Niu; Dongxing Shi; Hongmei Zhang; Lifang Zhao; et al. (Environmental Science and Pollution Research, 2024)

Structure-defined viologen-polyoxometalate modified separator dominating endurable Li-S batteries by a synergistic adsorption-electrocatalysis mechanism - Yuxi Zhang; Yundong Cao; Linlin Fan; Guilin Shi; Tianyu Zheng; Hong Liu; Jian Song; Guanggang Gao (Chemical Engineering Journal, 2024)

In vitro and in vivo anti-oomycetes activities and mechanisms of linalool against Saprolegnia ferax - Tao Tang; Weiming Zhong; Linlin Yang; Mingwang He; Sifan Jiang; Dan Yin; Jiajing Guo; Zhipeng Gao (Aquaculture, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessing the impact of marketization on energy poverty - Xinjie Shi; Pei Zeng; Liu Cui; Xuwen Gao; Tongwei Qiu; Qiang Jiang; Linlin Fu (Environment, Development and Sustainability, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

The effect of commercial β-glucosidase and its immobilization on quality of red wine production - Jun Wang; Linlin Ma; Hengfang Gao; Xia Li; Zhigang Dong (Biocatalysis and Agricultural Biotechnology, 2023)

A lipidomic approach to bisphenol F-induced non-alcoholic fatty liver disease-like changes: altered lipid components in a murine model - Xinjing Wang; Linlin Wu; Jingxian Tao; Heyong Ye; Jun Wang; Rong Gao; Wenwei Liu (Environmental Science and Pollution Research, 2023)

Frequency specific alterations of the degree centrality in patients with acute basal ganglia ischemic stroke: a resting-state fMRI study - Hao Chen; Linlin Zhan; Qianqian Li; Chaoguo Meng; Xuemei Quan; Xiaoling Chen; Zeqi Hao; Jing Li; Yanyan Gao; Huayun Li; Xize Jia; Mengting Li; et al. (Brain Imaging and Behavior, 2023)
This study intended to investigate the frequency specific brain oscillation activity in patients with acute basal ganglia ischemic stroke (BGIS) by using the degree centrality (DC) method. A total of 34 acute BGIS patients and 44 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning. The DC values in three frequency bands (conventional band: 0.01–0.08 Hz, slow‑4 band: 0.027–0.073 Hz, slow‑5 band: 0.01–0.027 Hz) were calculated. A two-sample t -test was used to explore the between-group differences in the conventional frequency band. A two-way repeated-measures analysis of variance (ANOVA) was used to analyze the DC differences between groups (BGIS patients, HCs) and bands (slow‑4, slow‑5). Moreover, correlations between DC values and clinical indicators were performed. In conventional band, the DC value in the right middle temporal gyrus was decreased in BGIS patients compared with HCs. Significant differences of DC were observed between the two bands mainly in the bilateral cortical brain regions. Compared with the HCs, the BGIS patients showed increased DC in the right superior temporal gyrus and the left precuneus, but decreased mainly in the right inferior temporal gyrus, right inferior occipital gyrus, right precentral, and right supplementary motor area. Furthermore, the decreased DC in the right rolandic operculum in slow-4 band and the right superior temporal gyrus in slow-5 band were found by post hoc two-sample t -test of main effect of group. There was no significant correlation between DC values and clinical scales after Bonferroni correction. Our findings showed that the DC changes in BGIS patients were frequency specific. Functional abnormalities in local brain regions may help us to understand the underlying pathogenesis mechanism of brain functional reorganization of BGIS patients.

A two-centennial perspective on spatially compounding hydroclimate events in arid and semi-arid north China - Qian Li; Linlin Gao; Yang Deng; Xiang Zhang; Yongkang Duan; Xiaohua Gou (Quaternary Science Reviews, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Turbulence behaviors underlying the sensible heat and water vapor flux dissimilarity in a stably stratified flow - Xiaofeng Guo; Wei Yang; Jinkyu Hong; Linlin Wang; Zhiqiu Gao; Degang Zhou (Environmental Fluid Mechanics, 2023)

A uniform methodology of local cooling and warming effects for different urban site types: multi-perspective assessment based on four northern Chinese cities - Jianfeng Gao; Qingyan Meng; Die Hu; Linlin Zhang; Xinli Hu; Jiangkang Qian (Sustainable Cities and Society, 2023)

Characteristics of anthropogenic heat with different modeling ideas and its driving effect on urban heat islands in seven typical Chinese cities - Jiangkang Qian; Qingyan Meng; Linlin Zhang; Uwe Schlink; Xinli Hu; Jianfeng Gao (Science of The Total Environment, 2023)

Anthropogenic heat variation during the COVID-19 pandemic control measures in four Chinese megacities - Qingyan Meng; Jiangkang Qian; Uwe Schlink; Linlin Zhang; Xinli Hu; Jianfeng Gao; Qiao Wang (Remote Sensing of Environment, 2023)

Dualistic cascade convolutional neural network dedicated to fully PolSAR image ship detection - Gui Gao; Qilin Bai; Chuan Zhang; Linlin Zhang; Libo Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

In vitro gastrointestinal digestion of whole grain noodles supplemented with soluble dietary fiber and their effects on children fecal microbiota - Linlin Gao; Lin Zhang; Huan Liu; Jielun Hu (Food Bioscience, 2023)

Elevation-dependent tree growth response to recent warming and drought on eastern Tibetan Plateau - Dingcai Yin; Xiaohua Gou; Haijiang Yang; Kai Wang; Jie Liu; Yiran Zhang; Linlin Gao (Climatic Change, 2023)

Influence of monsoon anomalies on intra-annual density fluctuations of Chinese pine in the Loess Plateau - Shuangjuan Wang; Yang Deng; Linlin Gao; Yuhang Zhang; Xingying Shi; Xiaohua Gou (International Journal of Biometeorology, 2023)

Long-term performance study applying a tandem AnSBR-ASBR to treat wastewater containing N, N-dimethylformamide: Sludge physicochemical properties, microecology, and functional genes - Linlin Cao; Chengyuan Su; Yiying Lu; Jinyan Wu; Lixin Wei; Junjie Liao; Yunchuan Xian; Shu Gao (Journal of Environmental Chemical Engineering, 2023)

Use of iron-loaded biochar to alleviate anammox performance inhibition under PFOA stress conditions: Integrated analysis of sludge characteristics and metagenomics - Linqin Tang; Chengyuan Su; Qing Wang; Linlin Cao; Yunchuan Xian; Shitong Wen; Yijie Zhou; Shu Gao (Science of The Total Environment, 2023)

Pre-monsoon drought variability in the southeastern Loess Plateau over the past 246 years - Yongkang Duan; Shuangjuan Wang; Yang Deng; Linlin Gao; Shuhua Qiao; Xiaohua Gou (Quaternary International, 2023)

Insight into the design and construction of Cr substituted Co-based columnar activated coke catalysts for effective and reliable removal of methylbenzene and Hg0 concurrently - Lei Gao; Lei Yi; Dong Xie; Hanqing Wang; Caiting Li; Linlin Li; Yijin Liu; Jinke Xie; Yihui Zhou; Yingyun Liu (Fuel, 2023)

Interaction mechanisms of fouling and cleaning protocol for A/O-MBR treatment of coal⁃to⁃hydrogen wastewater - Fang Gao; Lingyun Li; Yanwei Shi; Xiaofei Xue; Jianhua Mao; Linlin Xing; Xiaoyan Yao (Process Safety and Environmental Protection, 2023)

Divergent responses of Qinghai spruce (Picea crassifolia) to recent warming along elevational gradients in the central Qilian Mountains, Northwest China - Weiguo Zhang; Xiaohua Gou; Fen Zhang; Wenhuo Liu; Yun Zhang; Linlin Gao (Journal of Geographical Sciences, 2023)

Whether increased water‐use efficiency of Picea crassifolia promotes radial growth of trees in the eastern Qilian Mountains - Kai Wang; Xiaohua Gou; Linlin Gao; Wenhuo Liu; Haowen Fan; Weiguo Zhang; Haijiang Yang (International Journal of Climatology, 2022)
Global change, characterized by elevated atmospheric CO 2 concentrations and warming, is profoundly affecting terrestrial forests. However, whether the increasing atmospheric CO 2 concentration has a fertilizer effect on tree growth and whether intrinsic water use efficiency (iWUE) promotes tree growth in semi‐arid regions is not entirely clear. In this study, we evaluated the relationships between tree‐ring widths, δ 13 C values and iWUE of Qinghai Spruce ( Picea crassifolia Kom.) in the eastern Qilian Mountains, northwestern China. We found that the iWUE is significantly consistent with the δ 13 C of rings in the high‐frequency signal, and the relationship between iWUE and tree‐ring width is unstable. The first‐order difference correlation analysis with meteorological data showed that both the iWUE and tree‐ring width were drought‐limited. The radial growth was mainly regulated by water availability in current April and July, while annual variation of iWUE was primarily controlled by that in current July. In the early stage of trees growth, there was a positive relationship between iWUE and radial growth due to the CO 2 fertilization. During the 1970s–2000s, the effect of water availability in July on radial growth increases because of the decreased precipitation in July. This has decreased stomatal conductance, intercellular CO 2 concentration, carbon uptake and growth, contributing to the negatively significant correlation between tree‐ring widths and iWUE ( p

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

High Genetic Connectivity Inferred from Whole-Genome Resequencing Provides Insight into the Phylogeographic Pattern of Larimichthys polyactis - Jian Zheng; Linlin Zhao; Xiang Zhao; Tianxiang Gao; Na Song (Marine Biotechnology, 2022)

Chromosomal Assembly of the Hexagrammos agrammus Genome via Third-Generation DNA Sequencing and Hi-C Technology - Linlin Zhao; Shenghao Liu; Shouqiang Wang; Tianyan Yang; Qi Liu; Tianxiang Gao (Frontiers in Marine Science, 2022)

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Katabatic Flow Structures Indicative of the Flux Dissimilarity for Stable Stratification - Xiaofeng Guo; Wei Yang; Zhiqiu Gao; Linlin Wang; Jinkyu Hong; Baohong Ding; Long Zhao; Degang Zhou; Kun Yang (Boundary-Layer Meteorology, 2022)

Save reservoirs of humid subtropical cities from eutrophication threat - Meijie Liu; Xiaoyu Lei; Yanyan Zhou; Jingsi Gao; Yun Zhou; Linlin Wang; Jia Zhu; Xian-zhong Mao (Environmental Science and Pollution Research, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Phylogenomics Based on Transcriptome Data Provides Evidence for the Internal Phylogenetic Relationships and Potential Terrestrial Evolutionary Genes of Lungfish - Linlin Zhao; Shouqiang Wang; Fangrui Lou; Tianxiang Gao; Zhiqiang Han (Frontiers in Marine Science, 2021)
The evolutionary relationships of lungfish can provide crucial information on the transition from Sarcopterygii to tetrapods. Phylogenomics is necessary to explore accurate internal phylogenetic relationships among all lungfish species. In the context of the lack of genome-wide genetic information for Protopterus amphibious , we are the first to systematically report the transcriptome of P. amphibius and these sequences can be used to enrich the genome-wide genetic information of lungfish. Meanwhile, we also found significant differences in the expression levels of 3,189 genes between the lung and heart of P. amphibious . Based on phylogenomics, 1,094 shared orthologous genes were identified and then applied to reconstruct the internal phylogenetic structure of lungfish species. The reconstructed phylogenetic relationships provide evidence that lungfish is the sister group of terrestrial vertebrates and that Neoceratodus forsteri is the most primitive lungfish. Moreover, the divergence time between the most primitive lungfish and other lungfish species is between 186.11 and 195.36 MYA. Finally, 43 protein metabolism-related, stress response-related, and skeletogenesis-related genes were found to have undergone positive selection and fast evolution in N. forsteri . We suspected that these genes possibly helped ancient fish adapt to the new terrestrial environment and ultimately contributed to its spreading to land.

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

PbrPOE21 inhibits pear pollen tube growth in vitro by altering apical reactive oxygen species content - Ming Qian; Linlin Xu; Chao Tang; Hao Zhang; Hongru Gao; Peng Cao; Hao Yin; Lei Wu; Juyou Wu; Chao Gu; Shaoling Zhang (Planta, 2020)

Multi‐century drought variability in the southern Min Mountains - Xiaoya Yan; Yang Deng; Haowen Fan; Jiajia Su; Linlin Gao; Xiaohua Gou (International Journal of Climatology, 2020)
Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis , was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics.

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

Wheat methionine sulfoxide reductase A4.1 interacts with heme oxygenase 1 to enhance seedling tolerance to salinity or drought stress - Pengcheng Ding; Linlin Fang; Guangling Wang; Xiang Li; Shu Huang; Yankun Gao; Jiantang Zhu; Langtao Xiao; Jianhua Tong; Fanguo Chen; Guangmin Xia (Plant Molecular Biology, 2019)

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

Role of Exogenous Glutathione in Alleviating Abiotic Stress in Maize (Zea mays L.) - Laming Pei; Ronghui Che; Linlin He; Xingxing Gao; Weijun Li; Hui Li (Journal of Plant Growth Regulation, 2019)

Identification of protein arginine methyltransferase 7 (PRMT7) inhibitor by virtual screening and biological evaluation in vitro - Linlin Liu; Xiaoning Kai; Qingqing Chen; Ling Zhang; Ruosi Yao; Jian Gao (Medicinal Chemistry Research, 2019)

Constitutive activation of β-catenin in ameloblasts leads to incisor enamel hypomineralization - Linlin Fan; Shijian Deng; Xin Sui; Mengmeng Liu; Shuhua Cheng; Yunfei Wang; Yuguang Gao; Chun-Hung Chu; Qi Zhang (Journal of Molecular Histology, 2018)

The impact of urbanization on wind speed and surface aerodynamic characteristics in Beijing during 1991–2011 - Junkai Liu; Zhiqiu Gao; Linlin Wang; Yubin Li; Chloe Y. Gao (Meteorology and Atmospheric Physics, 2018)

Difference of acute dissociation and 1-day culture on the electrophysiological properties of rat dorsal root ganglion neurons - Yuanlong Song; Miaomiao Zhang; Xiaoqing Tao; Zifen Xu; Yunjie Zheng; Minjie Zhu; Liangpin Zhang; Jinhan Qiao; Linlin Gao (Journal of Physiology and Biochemistry, 2018)

Time-Dependent Lactate Production and Amino Acid Utilization in Cultured Astrocytes Under High Glucose Exposure - Dan Wang; Liangcai Zhao; Hong Zheng; Minjian Dong; Linlin Pan; Xi Zhang; Huajie Zhang; Hongchang Gao (Molecular Neurobiology, 2018)

Spatiotemporal drought variability of the eastern Tibetan Plateau during the last millennium - Yang Deng; Xiaohua Gou; Linlin Gao; Meixue Yang; Fen Zhang (Climate Dynamics, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Assessing the influences of tree species, elevation and climate on tree-ring growth in the Qilian Mountains of northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Meixue Yang; Fen Zhang (Trees, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Estimate of Boundary-Layer Depth Over Beijing, China, Using Doppler Lidar Data During SURF-2015 - Meng Huang; Zhiqiu Gao; Shiguang Miao; Fei Chen; Margaret A. LeMone; Ju Li; Fei Hu; Linlin Wang (Boundary-Layer Meteorology, 2017)

Identification of forty-five gene-derived polymorphic microsatellite loci for the sea cucumber, Apostichopus japonicus - MENG CHEN; LINLIN GAO; WEIJIE ZHANG; HONGZHENG YOU; QIAN SUN; YAQING CHANG (Journal of Genetics, 2016)

Recent reduction in the frequency of frost accounts for most of the increased growth of a high elevation spruce forest in northwestern China - Richard H. Waring; Linlin Gao (Trees, 2016)

Tree‐ring recorded drought variability in the northern Min Mountains of northwestern China - Yang Deng; Xiaohua Gou; Linlin Gao; Fen Zhang; Xiangyu Xu; Meixue Yang (International Journal of Climatology, 2016)
Drought is a recurrent natural disaster in northwestern China and it can have a substantial impact on the affected region; therefore, knowledge of drought variability is very important for drought adaptation and mitigation. However, the observed climate data are generally limited in length, which may hamper our understanding the full range of drought variability. Using tree‐ring width measurements of 155 series from 81 Pinus tabulaeformis trees at three sites in the northern Min Mountains of northwestern China, the standardized precipitation evapotranspiration index ( SPEI ) for May–August from 1804 to 2011 were reconstructed, which account for 64.8% of the variance in the instrumental record over 1954–2011. The new reconstruction is generally consistent with other moisture reconstructions nearby. Two notable features of the SPEI reconstruction is the severe drought starting in the late 1990s and the gradual drying trend since 1954. These features are also apparent in areas located in the north boundaries of Eastern Asian Summer Monsoon ( EASM ), which indicates that the study area may be affected by the EASM .

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Forward modeling analyses of Qilian Juniper (Sabina przewalskii) growth in response to climate factors in different regions of the Qilian Mountains, northwestern China - Junzhou Zhang; Xiaohua Gou; Yongxiang Zhang; Ming Lu; Xiangyu Xu; Fen Zhang; Wenhuo Liu; Linlin Gao (Trees, 2016)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Millennium tree-ring reconstruction of drought variability in the eastern Qilian Mountains, northwest China - Xiaohua Gou; Yang Deng; Linlin Gao; Fahu Chen; Edward Cook; Meixue Yang; Fen Zhang (Climate Dynamics, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

An 850‐year tree‐ring‐based reconstruction of drought history in the western Qilian Mountains of northwestern China - Xiaohua Gou; Linlin Gao; Yang Deng; Fahu Chen; Meixue Yang; Christopher Still (International Journal of Climatology, 2015)
Studies of regional drought history will be helpful for understanding current hydroclimate variability with global warming as well as predicting future hydroclimate shifts. Long‐term tree‐ring records are scarce in the western Qilian Mountains of northwestern China, which is also the western boundary of the natural distribution of Qilian Juniper ( Juniperus przewalskii Kom.) in this area. Here, we present an 850‐year ( AD 1161 –2010) reconstruction of May–July self‐calibrating Palmer Drought Severity Index ( scPDSI ) in the western Qilian Mountains that is based on two nearly millennia of ring‐width chronologies derived from long‐lived Qilian Juniper trees. The reconstruction suggests a relatively dry phase from the 15th century to the 18th century during the Little Ice Age ( LIA ) and a relatively wet period over the past two centuries. This reconstruction is consistent with other tree‐ring‐based hydroclimatic reconstructions from the northeastern Tibetan Plateau, as well as the corresponding century‐scale solar activity during the LIA . The three mega‐drought periods ( AD 1260s –1340s, 1430s–1540s and 1640s–1740s) recorded by the tree‐ring series also correspond to the Wolf, Spörer and Maunder solar activity minimum periods. Results of the multi‐tape method analysis and wavelet analysis further confirmed the relationship between regional hydroclimate variability and solar activity forcing.

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

Erratum to: Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Calcium accumulation characterization in the aerobic granules cultivated in a continuous-flow airlift bioreactor - Dandan Zhou; Mengyuan Liu; Linlin Gao; Chunyan Shao; Jie Yu (Biotechnology Letters, 2013)

Climate–growth analysis of Qilian juniper across an altitudinal gradient in the central Qilian Mountains, northwest China - Linlin Gao; Xiaohua Gou; Yang Deng; Wenhuo Liu; Meixue Yang; Zhiqian Zhao (Trees, 2013)

Influence of algal bloom degradation on nutrient release at the sediment–water interface in Lake Taihu, China - Mengyuan Zhu; Guangwei Zhu; Linlin Zhao; Xin Yao; Yunlin Zhang; Guang Gao; Boqiang Qin (Environmental Science and Pollution Research, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)

Purification and characterization of an extracellular poly(3-hydroxybutyrate-co-3-hydroxyvalerate) depolymerase from Acidovorax sp. HB01 - Zhanyong Wang; Jia Gao; Linlin Li; Husheng Jiang (World Journal of Microbiology and Biotechnology, 2012)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)